Determinación del efecto de la consaguinidad en la producción de leche de vacas gyr y girolando en la ganadería Santa Amalia, ubicada en Santo Domingo de los Tsáchilas, Ecuador - Coronel Miño, Nataly Elizabeth (2023)
In the Santa Amalia Livestock Farm located in Santo Domingo de los Tsáchilas, Ecuador at 655 masl, the genealogical record and milk production of 120 Gyr and Girolando cows were carried out, the data were purified in Excel, after that they are analyzed using the Incomplete Gamma function in the SAS, vw 9.4 (2014). The comparison of the least square means was made through the PROC MEANS and the correlation of the milk production characters through the CORR procedure and the correlation of consanguinity and milk production traits using the Pedigree Viewer program; The proposed objectives were: 1) Calculate the consanguinity of the animals in the Santa Amalia livestock 2) Establish the effect of consanguinity on milk production characters. The variables and results evaluated were; Milk production/day was determined between 18.66 ±0.54kg and 15.96 ±0.45kg; Total milk production was 7513.0 ±65.75kg; Total milk production was 7513.0 ±65.75kg; In the duration of lactation the data had a variation expressed in relative values in the mean less than 26.90%; the data that were very pronounced were 12.88, they were overloaded to the right of the mean (10.88); the correlations between consanguinity and total milk_ LTOTAL was 49.79%, considered as low (40 to 60). According to the results that have been obtained, the null hypothesis was rejected and the alternative hypothesis was accepted, it is concluded with this investigation determining that consanguinity shows a high value of significance which can affect milk production in Livestock.